2010
DOI: 10.1007/s12272-010-1110-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of terpenes on percutaneous absorption of tiaprofenic acid gel

Abstract: Tiaprofenic acid is a potent analgesic and nonsteroidal anti-inflammatory drug (NSAID) and like any other nonsteroidal anti-inflammatory drug, oral administration of the conventional dosage forms of tiaprofenic acid invariably causes gastrointestinal side effects. In an effort to eliminate these side effects while enhancing the drug concentration at the target tissue, an epidermal application of tiaprofenic acid seems to be an effective alternative drug delivery modality. This study attempts to demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Aside from occupational health issues, studying the behavior of nanoparticles with the skin barrier is a very important basic research approach for later application in designing topical drug delivery systems with optimal parameters. This is especially true when solvents like terpenes are used in topical formulations (38). Our experimental design was congruent with previous gold nanoparticle skin penetration studies with similar exposure times and use of static Franz cells.…”
Section: Discussionsupporting
confidence: 75%
“…Aside from occupational health issues, studying the behavior of nanoparticles with the skin barrier is a very important basic research approach for later application in designing topical drug delivery systems with optimal parameters. This is especially true when solvents like terpenes are used in topical formulations (38). Our experimental design was congruent with previous gold nanoparticle skin penetration studies with similar exposure times and use of static Franz cells.…”
Section: Discussionsupporting
confidence: 75%
“…Studies on the percutaneous absorption of different drugs in the presence of terpenes have suggested that the effects of the latter are related to their concentration and chemical characteristics …”
Section: Discussionmentioning
confidence: 99%
“…Compounds that can reversibly change the SC barrier properties have been widely described as penetration enhancers (P.Es). Terpenes are naturally occurring compounds found in essential oils that have been explored as skin penetration enhancers (P.E); that is, they can improve the penetration of drugs into the skin by altering the composition or organization of the lipid membrane, thus allowing the diffusion of the drug through the skin . Their effects depend on both the drug and terpene lipophilicity, and they may promote the permeability of hydrophilic or lipophilic drugs …”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that topical NSAIDs require overall less active drug vis-à-vis the dosage of systemic NSAIDs. Therefore, topical therapy is not only promising on the safety and efficacy fronts but also on the economic fronts too [38]. The various advantages of topical delivery are enlisted in Table 1.…”
Section: Need Of Nonoral Deliverymentioning
confidence: 99%
“…The physicochemical factors of drug like log P , pK a , solubility, and molecular mass also play an important role in the selection of components for the topical delivery vehicle [36, 40]. For acidic and unstable drugs like ACE, special consideration has to be made on the excipient selection for topical vehicle which will not only mask the irritation potential of ACE due to acidic group but also provide milieu for effective topical delivery and maintenance of chemical integrity [35, 38]. Figure 3 highlights the various challenges offered by ACE while developing an ideal topical formulation.…”
Section: Challenges In Topical Deliverymentioning
confidence: 99%